Communication in the Mirror of Social Semiotics - N. V. Kazarinova (Дискурс, 2024)
Introduction. The subject of this article is communicative resources, which are selected by partners from a huge variety of linguistic means, functional styles, rhetorical techniques, and subject activities, and through which a common semantic space between individuals is generated.Methodology and sources. As a methodological platform we propose the principles of praxis-oriented social semiotics. Being one of the relatively late trends of semiotic research, social semiotics focuses attention not so much on signs or sign systems as on social signifying practices as regular, repetitive, recognisable types of actions: the actions of communication participants are endowed with the properties of sign systems through which relations between individuals are discovered, made visible and meaningful. The mechanisms of meaning production, from the point of view of the participants of the event, are analysed using the concept of ‘discursive practices’, understood as speech actions in order to solve a variety of practical interpersonal tasks.Results and discussion. As an individual learns a variety of interpersonal discursive practices, different relational systems become available to him/her. Specific discursive practices allow individuals to present different versions of their self, justify their actions, maintain dominance and/or subordination relations, thus demonstrating mastery of the communicative situation. Following the principles of praxis-oriented social semiotics, it can be argued that interpersonal relationships involve what can be called a discourse of trust, personal involvement in relationships, intimacy/closeness.Conclusion. The described symbolic regulators allow not only to semiotically comprehend the social positions of interacting parties, but also to offer self-control procedures and an arsenal of communicative actions to the participants of interpersonal communication as means of behaviour management in situations of interpersonal communication.